Immobilization of β‐Glucosidase BglC on Decanedioic Acid‐Modified Magnetic Nanoparticles. Issue 10 (3rd September 2018) - Wang, Nuo; Wu, Rina; Fu, Qiang; Wang, Hongling; Zhang, Zheng; Haji, Ze; Li, Xiutong; Lian, Xinglong; An, Yingfeng
Abstract: β ‐Glucosidase BglC from Thermobifida fusca was efficiently immobilized on decanedioic acid‐modified magnetic nanoparticles (DMNP). Interestingly, the immobilized BglC showed much higher organic solvent stability than the free enzyme, indicating that this enzyme immobilized on DMNP should be especially suitable for catalyzing reactions in organic solvents. Additionally, the immobilized BglC also showed better thermal stability, storage stability, and mechanical stability than the free counterpart. Moreover, the reuse times were satisfactory and even crude plant materials (e.g., rice husk and corn cob) were used as substrates, which should be valuable for the decomposition of natural organic materials and the full utilization of bioresources. Abstract : Thermobifida fusca β ‐glucosidase BglC immobilized on decanedioic acid‐modified magnetic nanoparticles shows higher organic solvent stability, thermal stability, storage stability, and mechanical stability than the free enzyme. Reuse times were good even with crude plant materials as substrates, favoring the decomposition of natural organic materials and the full utilization of bioresources.